ANALYSIS OF OPERATIONAL PERFORMANCE OF MICROTRANS JAK 47 CIGANJUR – PASAR MINGGU - Wita Meutia; Prima Jiwa Osly; Ariq Syawal Nugroho (Jurnal Infrastruktur, 2025)
Transportation is an important aspect in supporting the economy and helping community activities. To deal with the increasing mobility of the community, the DKI Jakarta provincial government in collaboration with PT Transportasi Jakarta has innovated to create a transportation program called Jaklingko. Currently, the Jaklingko microtrans already has 83 routes, one of which is the Jak 47 route which operates in the Ciganjur - Pasar Minggu area, South Jakarta. The service of route 47 seems to be unable to serve well which causes a buildup of users during peak hours so that the load factor increases. The purpose of this study is to analyze operational performance and analyze the existing performance of the Jak 47 microtrans. Data collection was carried out using a field survey method in the form of a dynamic survey and a static survey. Then the survey results will be compared with the 2002 Minimum Service Standards (SK Ditjen Hubdat No.687 / AJ.206 / DRJD / 2002). Based on the results of the analysis, operational performance indicators such as load factor, headway, travel time, speed and frequency have performed well.